Pre‐adolescent children's experiences of receiving diabetes‐related support from friends and peers: A qualitative study - Rankin, David (Health Expect, 2018)
BACKGROUND: While pre‐adolescent children with type 1 diabetes receive most support from their parents/caregivers, others also contribute to their care. This study explored pre‐adolescent children's experiences of receiving diabetes‐related support from friends and peers. The objective was to identify how children could be better supported by their friends and peers to undertake diabetes self‐management. METHODS: In‐depth interviews with 24 children (aged 9‐12 years) with type 1 diabetes. Data were analysed using an inductive, thematic approach. RESULTS: Children gave mixed accounts of their experiences of speaking to their school/class about diabetes with some indicating that this had resulted in unwanted attention. Most individuals reported that other children had a limited understanding of diabetes and sometimes acted in insensitive ways or said things they found upsetting. Virtually all children described having a small number of close friends who were interested in learning about diabetes and provided them with support. These friends provided support in three overlapping ways, as “monitors and prompters,” “helpers” and “normalizers.” While some children described benefiting from meeting peers with type 1 diabetes, most indicated that they would prefer to develop friendships based on shared interests rather than a common disease status. DISCUSSION AND CONCLUSIONS: Friends and peers provide several kinds of support to pre‐adolescent children with diabetes. Health professionals could consider ways to assist small friendship groups to undertake monitoring and prompting, helping and normalizing roles. Parents, schools and health professionals could explore ways to normalize self‐management practices to better support children with diabetes in school settings.